Partnerships between Public Schools and Private Developers. A Report of the Joint Legislative Audit Committee - Armoudian, Maria; California State Legislature, Sacramento. Joint Legislative Audit Committee ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
The California Legislature's Joint Legislative Audit Committee investigated several "joint venture" partnerships between school districts and the private sector to develop school district-owned properties to determine the feasibility of such innovative school construction projects. This report presents findings from seven of these public/private joint ventures along with the activities of the consultants, attorneys, and district staff who promoted, planned, and attempted to execute them. The report reveals that in all seven cases, school districts encountered significant problems and complications that appear to far outweigh the benefits that these projects' proponents promised to the school districts. Evidence suggests that the Los Angeles Unified School District joint venture operation in particular, being largely unsupervised and virtually unaccountable, engaged in irresponsible, and possibly illegal, behavior by consistently misrepresenting basic facts in order to gamble public funds on highly speculative projects. The report indicates that these abuses have misdirected and squandered millions of taxpayers dollars intended for instructional programs and the rebuilding of the public education infrastructure. An appendix presents a timeline on the Brea Olinda High School and Belmont Learning Complex joint venture projects. (GR)
Availability: Web site: http://democrats.assembly.ca.gov/members/a43/jlac.htm (full text).
ERIC Note: For other Joint Legislative Audit Committee Reports, see ED 005 595-600. Cover title: "Partnerships between Public Schools and Private Developers. An Investigative Report.".
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administration; Elementary Secondary Education; Legal Responsibility; Partnerships in Education; Private Sector; Public Schools; School Construction; School District Spending; State School District Relationship; Los Angeles Unified School District CA; Reports, Evaluative